SUSTAINABLE MARKETING OF UKRAINIAN AGRI-LOGISTICS UNDER ESG TRANSFORMATION OF EXPORTS - Shkoryna, Ihor; Ruzhynskas, Oleksandr (Current Problems of Sustainable Development, 2026)
The article addresses the emerging system of sustainable marketing of logistics services in the agro-industrial complex (AIC) of Ukraine, considered in the context of the deep transformation of the European regulatory environment. The Corporate Sustainability Reporting Directive (CSRD), the European Sustainability Reporting Standards (ESRS), the Carbon Border Adjustment Mechanism (CBAM) and the European Green Deal collectively reshape the value proposition of Ukrainian agri-exporters by linking market access in the European Union to verifiable environmental, social and governance (ESG) performance throughout the supply chain. The purpose of the article is to provide a conceptual substantiation of a model of sustainable marketing of export-oriented agri-logistics that integrates ecological verifiability, social responsibility, and transparent corporate governance with the pragmatic constraints of a crisis-driven economy. The methodological framework combines systemic, comparative, and content analysis with an institutional perspective on the secondary pressure exerted on Ukrainian exporters by European buyers, financial institutions, and regulators. Empirically, the study refers to the transformation of Ukrainian agricultural export corridors after the full-scale Russian invasion of 2022, including the EU Solidarity Lanes, the Danube route and the renewed Ukrainian Black Sea corridor, and to the institutionalisation of ESG reporting at leading Ukrainian agro-industrial companies. The article identifies the structural ESG-related differentiators in Ukrainian agrilogistics marketing, discusses the risk of greenwashing as a barrier to authentic sustainable communication, and formulates a four-component verification framework (measure, reduce, offset, communicate). Practical recommendations for Ukrainian logistics operators of agricultural products are proposed, including the integration of GRI-aligned sustainability disclosure into marketing assets, embedding verified ESG indicators into service-level agreements, and the development of authentic sustainability brand positioning.